The Effect Of Work Life Balance On Nurses' Job Satisfaction In Hospitals : Literature Review - Alifia Nasywa Ardafiani (CV. AFDIFAL MAJU BERKAH, 2026)
Work life balance is an important aspect that can affect the job satisfaction of health workers, especially nurses. Knowing the influence work life balance on health workers, especially nurses in hospitals, on the job satisfaction they get. This study uses a literature review methodology, by reviewing relevant articles from google scholar, science direct, springer link, and portal Garuda using the search keyword Work life Balance and Impact and Hospital and Health workforces or Health Workers and Job and Satisfaction with journal inclusion criteria published at least the last 5 years, open access, and relevant to the objectives of the research to be carried out. 6 articles relevant to the research were obtained from national articles. This review focuses on the balance between work and personal life that can affect positive the level of job satisfaction and the quality of service that will be provided by health workers on organizational performance with the results showing that WLB generally has a significant effect on nurse job satisfaction. However, there is a negative influence obtained from other factors originating from individuals, organizations and the environment such as job stress, burnout, compensation and intrinsic motivation. The article obtained that there is an influence of work life balance on job satisfaction of health workers which contributes positively. However, it is not the only determinant of nurses' job satisfaction, but various other factors that influence each other.